Finding Goal Focus With People With Severe Traumatic Brain Injury in a Person-Centered Multi-Component Community Connection Program (M-ComConnect) - Leeson, Rebecca; Collins, Michelle; Douglas, Jacinta (Frontiers in Rehabilitation Sciences, 2021)
Background and objectives: Loss of social connections in the community is a common consequence of severe traumatic brain injury (TBI), resulting in reduced well-being and quality of life. M-ComConnect is an individualized multi-component community connection intervention with the key objectives of increasing social activity, developing social relationships and supporting community participation following severe TBI. As part of the M-ComConnect approach, semi-structured initial interviews were conducted to develop a holistic understanding of each participant and their goal focus for the project. In this paper we describe how clinicians worked with participants to identify a desired community-based social activity goal in which to participate. Method: Transcripts of initial interviews between participant and clinician were analyzed using the phases of reflexive thematic analysis outlined by Braun and Clarke (2006, 2019). Participants were ten individuals aged between 24-75 with severe TBI. All were living in the community and reported reduced social connections since their TBI. The aim of the analysis was to evaluate the skills and strategies used by clinicians in their interactions with participants to derive goal focus for the program. Results: Thematic analysis of initial interview data revealed three main categories and fourteen sub-categories of clinical strategies. These were: 1) Humanizing (curiosity; demonstrating respect and empathy; providing compliments and affirmations; simple reflections; revealing aspects of self; and humour and laughter), 2) Empowering (emphasizing choice and control; highlighting strengths; identifying roadblocks and reframing to reveal opportunities; and collaborative problem solving), and 3) Focusing (making suggestions; identifying preferences; working with ideas; and negotiating). These strategies aligned with the program’s relational approach and supported the core processes of the goal-focussing framework, namely understanding and connecting with you, building a relationship and working together with you to find focus. Conclusion: The goal-focusing framework and clinical strategies outlined provide guidance for clinicians working with people with TBI in the community and is a promising way to engage clients when focusing on individualized social activity-based goals.